Rickety Boats to Refuge(e): Migration, Gender, and Subjectivity Among Rohingya Refugee Women - Farhana Rahman (University of Darussalam Gontor Press, 2023)
As an ethnoreligious minority living in Myanmar’s Rakhine State, located in the western coastal region of the country, the Rohingya were stripped of their citizenship in Myanmar in 1982 and have lived without legal residency status in the country since. A fresh wave of deadly anti-Muslim violence in 2012 in Rakhine state by the Burmese Buddhists has resulted in increased displacement of the Rohingyas into inhumane settlements and camps. Facing the possibility of violence at the hands of the Myanmar army, many have left their homeland, hoping to find safety in neighbouring countries. The 2012 attacks in Rakhine state resulted in a drastic increase of women and girls undertaking boat journeys to escape intense violence – including mass sexual violence – targeted against the Muslim Rohingya community at the hands of the Buddhist majority. Through feminist ethnographic research, this project seeks to explore how forced migration and the mass exodus of the Rohingya community to Southeast Asia have transformed Rohingya gender relations and roles in displacement – specifically, how forced migration has affected the gendered subjectivities and lived experiences of Rohingya refugee women. The theoretical framework of this study lies at the junction of gender studies, anthropology, and studies in forced migration. It will engage with issues such as the body, gendered violence, culture, victimhood and agency, and social transformation. The current Rohingya refugee crisis exposes the failure of countries like Bangladesh and Malaysia to offer real protection to those fleeing from conflict and their various insecurities, especially regarding the continuum of violence during different phases of competition, flight, and encampment.